METANOSTRESS CONDITIONS FOR HYDROBIONTS - Lyushvin P.B.,; M. O, Buyanova (IJRDO - Journal of Applied Management Science, 2022)
When mass degassing of CH4 is activated, mainly seismogenic, young aerobic commercial fish and zoobenthos die, pelagic fish are thrown ashore, bottom fish float to the surface, rise to the surface and crustaceans go ashore. In surviving fish, reproductive functions are impaired. After mass emission of CH4, fishing clusters of fish disappear for a while - after information about emission, you should not go to the "affected" waters for fishing. Catches will be significantly lower than predicted and economically unprofitable, you can look for the "edges of affected" waters where the fish migrated, even when the conditions in them are not uncharacteristic for it, for example, in temperature, salinity, depth, feed base. After abnormally seismic years, there is a massive shift in the sexual composition of fish towards fat females with impaired reproductive functions, the non-viability of young fish is an increase in the number of crustaceans.For administrators, the recognition of seismostress anomalies means the problems of selling regional quotas for the extraction of hydrobionts and obtaining funds for fishing exploration. Hidden information about the seismogenic infertility of maternal herds led to the ruin of Barents, White sea, Caspian artless that bought "blown" quotas.The conclusions are based on the analysis of retrospective data on fish catches, crustaceans and mollusks in the economic waters of Russia, Taiwan, Peru, Chile, both in marine and fresh waters.